Ectopic Expression of Transcription Factor AP-2δ in Developing Retina: Effect on PSA-NCAM and Axon Routing - Li, Xiaodong (J Neurochem, 2013)
Retinal ganglion cells transmit the visual signal from the retina to the brain. We have previously shown that the AP-2δ (TFAP2D) transcription factor is expressed in one-third of ganglion cells in developing retina suggesting a specialized role for these AP-2δ-expressing cells. Here, we address the role of AP-2δ in retina by in ovo electroporation of RCAS/AP-2δ retroviral constructs into the eyes of chick embryos at day 2 of gestation. Ectopic expression of AP-2δ does not affect lineage differentiation in the developing retina. However, immunostaining of retinal tissue with markers associated with axonal growth such as GAP43 and PSA-NCAM demonstrates axonal misrouting and abnormal axonal bundling. Treatment of AP-2δ-misexpressing retinal cell cultures with Endo-N, an enzyme that removes PSA from NCAM, decreases AP-2δ-induced axonal bundling. Our data suggest a role for AP-2δ in polysialylation of NCAM, with ectopic expression of AP-2δ resulting in premature bundling of emerging axons and misrouting of axons. We propose that expression of AP-2δ in a subset of ganglion cells contributes to the fine-tuning of axonal growth in the developing retina.